The Study of Electronic States of Ni and ScI Molecules with Screened Kratzer Potential - Etido Inyang; Effiong Obisung (East European Journal of Physics, 2022)
In this study, the analytical solutions of the Schrödinger equation with the screened Kratzer potential model is solved using the well-known Nikiforov-Uvarov method. The energy spectrum and the normalized wave function with the Greene-Aldrich approximation to the centrifugal term are obtained. The energy spectrum is used to generate eigenvalues for X3Σ- state of NI and X1Σ+ state of ScI molecules respectively. The calculated results agree excellently with the experimental data. This research finds application in chemistry, industry, molecular physics and studies on magnetocaloric effect for several molecules. Our findings also demonstrate that the approximation scheme is well suited for this potential.